2012
DOI: 10.3389/fpls.2012.00099
|View full text |Cite
|
Sign up to set email alerts
|

Stiff Mutant Genes of Phycomyces Affect Turgor Pressure and Wall Mechanical Properties to Regulate Elongation Growth Rate

Abstract: Regulation of cell growth is paramount to all living organisms. In plants, algae and fungi, regulation of expansive growth of cells is required for development and morphogenesis. Also, many sensory responses of stage IVb sporangiophores of Phycomyces blakesleeanus are produced by regulating elongation growth rate (growth responses) and differential elongation growth rate (tropic responses). “Stiff” mutant sporangiophores exhibit diminished tropic responses and are found to be defective in at least five genes; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Also relevant in this context is the finding that some of the so‐called ‘stiff” mutants of Phycomyces with reduced gravitropic bending possess an increased turgor pressure but reduced rates of cell wall deformation (Ortega et al . ). An increased focus on the nanomechanics would very likely lead to integrative gravitropism concepts that have already been better explored for plants (reviewed in Baluska & Volkmann ).…”
Section: Phycomyces In the Context Of Fungal And Plant Graviresearchmentioning
confidence: 97%
See 2 more Smart Citations
“…Also relevant in this context is the finding that some of the so‐called ‘stiff” mutants of Phycomyces with reduced gravitropic bending possess an increased turgor pressure but reduced rates of cell wall deformation (Ortega et al . ). An increased focus on the nanomechanics would very likely lead to integrative gravitropism concepts that have already been better explored for plants (reviewed in Baluska & Volkmann ).…”
Section: Phycomyces In the Context Of Fungal And Plant Graviresearchmentioning
confidence: 97%
“…Cultures of Phycomyces cultivated for 19.5 days in microgravity in the Russian biosatellite Cosmos-782 maintained normal vegetative and sexual development, but had completely disoriented sporangiophores, forming twists and loops. The normal growth pattern of sporangiophores could be recovered on a centrifuge operating at an acceleration of 1 g (Parfyonov et al 1979). The effectiveness of gravitropism depends to some extent on the developmental stage, as stage 1 sporangiophores, which lack a sporangium ( Fig.…”
Section: Gravitropismmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased chitin synthase activity could explain the light growth response if newly synthesized chitin produces wall loosening by competing for load‐bearing bonds. Previously, it was shown that stiff mutant sporangiophores have shorter growth zones compared to wild type (Ortega et al, ). It may be deduced that the stiff mutant sporangiophores have less chitin synthase activity due simply to having shorter growing zone, or the shorter growth zones are the result of less chitin synthase activity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the mutants were termed “stiff” mutants, which indicate that the elastic deformation rate of the cell wall is reduced. Subsequent experimental research employing the pressure probe shows that the irreversible cell wall extensibility, ϕ , for stiff mutants C216 and C149 is significantly smaller than that of the wild type, but the magnitude of the critical turgor pressure, P c , is smaller as well (Ortega et al, ). The results indicate that the plastic deformation rate of the cell wall is reduced but the magnitude of the change could not be definitively determined.…”
Section: Introductionmentioning
confidence: 99%